Assumed Mechanism of Polymeric Deposit Formation in Recycle Propylene Washing Column during Bulk Polymerization; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Mayer E. A. Eduard Aleksandrovich; Trofimova A.; Mashukov V.; Pestryakov A. N. Aleksey Nikolaevich (Material Engineering and Technologies, 2015)
Title screen